Patterns of mobility, and the effect of mobility on viral suppression and retention among postpartum women living with HIV in South Africa - Mazriel, Robyn (Department of Public Health and Family Medicine, 2021)
Introduction: In South Africa postpartum women have been shown to be at high risk of disengagement from HIV care and postpartum mobility may be related to disruptions in care. This study aimed to describe patterns of mobility, and explore associations with viral suppression and retention in the postpartum period. Methods: This study used data from a prospective cohort study that enrolled women who initiated life-long antiretroviral therapy (ART) during their pregnancy in Gugulethu, Cape Town (March 2013 -June 2014), and an additional follow-up study at approximately 4 years postpartum. Patterns of self-reported mobility between delivery and the 4 year measurement visit were examined. Logbinomial models were used to explore the association between mobility (moving in the 3, 6 or 12 months prior to the study visit) and i) viral suppression (viral load (VL) ≤50 and ≤1000 copies/mL measured at the 12 month and 4 year measurement visit) and ii) retention in care (based on routine medical record data at approximately 12 months and 4 years postpartum). Results: Among the 353 women in this analysis, 98 (28%) reported having ever moved between delivery and 4 years postpartum. Mobility was more likely to occur soon after delivery with 50% of the moves occurring within the first year following delivery; the most common reason for moving being to live with and receive support from family (44%). Moving within 3 months of the viral load measurement at 12 months postpartum was associated with having a VL≤50 copies/mL (aRR=1.61, 95% CI: 1.17-2.21). Moving in any window prior to the 12 month or 4 year postpartum viral load was not associated with viral suppression. Retention in care at both 12 months and 4 years postpartum was not associated with mobility. Conclusions: These results demonstrate that movement following delivery is a common occurrence among postpartum women, but this movement did not seem to disrupt engagement in HIV care. There is a need for further research to understand the impact of this movement on postpartum women's viral suppression and retention in care, as well as on ways to support continued engagement in HIV care after delivery.